An Entropy-Based Approach to Introducing Osmotic Pressure - Ilan Shumilin; Levy, Yehonatan N.; Harries, Daniel (The Biophysicist, 2025)
We present a new approach to teaching the concept of osmotic pressure in physical chemistry courses. Our route is different from the traditional derivation that hinges on equating chemical potentials. Instead, we resort to the equivalent, yet more intuitive, concepts of mixing entropy and free energy and use their relation to the second law of thermodynamics. Our strategy emphasizes the role of entropically driven forces, which are a principal, yet underappreciated, theme in physical chemistry and biophysics. In doing so, we have extended the available examples of entropic forces that can be introduced to undergraduate chemistry and biology students.
[["fid":"31686","view_mode":"default","type":"media","attributes":"height":"152","width":"258","alt":"TOC figure","class":"media-element file-default"]]